THE EXPRESSIVE SPEECH ACT IN THE LOVELY BONES MOVIE - Irma Irma Tanjung (Jurnal Ilmiah Spectral, 2021)
This study aims at finding out the analysis of the types of expressive speech acts and the most dominant expressive speech acts used by characters in literary works. Qualitative methods were used to fulfill two research objectives. The data was collected from the movie that was taken from the utterances used by the characters. It was observed, selected, and classified. The researcher took notes as a tool to classify the expressive acts of the characters in the movie. The results showed that nine kinds of expressive expressions were found in the movie, namely apologizing, blaming, congratulating, doubting, greeting, praising, regretting, thanking, and wishing. The most dominant type of expressive action used is the praising act because the character performs this action when he admires someone or an object for the listener. In addition, giving praise to others can make others more motivated; giving praise has a calming effect and makes others feel valued, and increases the listener's confidence. It is expected that the result of this study can be used as references for future research.